THE STUDENT'S PERCEPTION OF REWARDS TO INCREASE THEIR MOTIVATION IN ENGLISH LEARNING IN JUNIOR HIGH SCHOOL - Maulana, Mohammad Deni Irkhamil; Budianto, Langgeng (English Edu: Journal of English Teaching and Learning, 2022)
The reward is a form of appreciation from the student pursuer to provide an inner emotional connection. The reward is a strategy in learning that functions as a stimulus and response to students in learning English effectively. The type of reward given to students varies greatly depending on the needs of students in learning, ranging from praise, grades, and nonverbal. All the variations of rewards in learning have a common goal of increasing student motivation in learning. This study aims to determine students' perceptions of reward strategies to increase motivation to learn English in junior high school. The respondents in this study were class VIII-A students at MTsN 8 Kediri for the 2021/2022 academic year. The number of respondents was 33 students in the bilingual class. Meanwhile, the research method used is a qualitative case study using questionnaires and interviews to obtain accurate data. This study shows that students give positive perceptions about learning to use rewards in increasing learning motivation. There are four kinds of rewards often used in learning English at MTsN 8 Kediri.